Multiomic analysis revealed the regulatory role of the KRT14 gene in eggshell quality - Wu, Yan; Sun, Yanyan; Zhang, Hao; Xiao, Hongwei; Pan, Ailuan; Shen, Jie; Pu, Yuejin; Liang, Zhenhua; Du, Jinping; Pi, Jinsong (Frontiers in Genetics, 2022)
Background: Eggshell strength and thickness are critical factors in reducing egg breaking rate and preventing economic losses. The calcite biomineralization process is very important for eggshell quality. Therefore, we employed transcriptional sequencing and proteomics to investigate the differences between the uteruses of laying hens with high- and low-breaking-strength shells. Results: A total of 1028 differentially expressed genes (DEGs) and 270 differentially expressed proteins (DEPs) were identified. The analysis results of GO terms and KEGG pathways showed that most of the DEGs and DEPs were enriched in vital pathways related to processes such as calcium metabolism, hormone and amino acid biosynthesis, and cell proliferation and apoptosis. Several DEGs and DEPs that were coexpressed at mRNA and protein levels were verified. KRT14 (Keratin-14) is a candidate gene (protein) obtained by multiple omics analysis due to the fold difference of KRT14 was the largest. After the overexpression of KRT14 in uterine epithelial cells, the expression of OC116 (Ovocleididin-116), CALB1 (calbindin 1), BST1 (ADP-ribosyl cyclase 2) were found to be increased significantly, while the expression of OC17 (Ovocleididin-17) was found to be decreased significantly. Conclusion: In summary, this study confirms that during normal calcification, there are differences in ion transport between the uterus of hens producing high-breaking-strength eggshells and those producing low-breaking-strength eggshells, which may help to elucidate the eggshell calcification process. The KRT14 gene may promote calcium metabolism and the deposition of calcium carbonate in eggshells.